Pattern of femoro-popliteal aneurysms in an African population - Ogeng'o,Julius A (2010)
Objective: To describe the pattern of femoro-popliteal aneurysms in an African Kenyan population. Patients and methods: Records of African in-patients with diagnosis of femoral or popliteal aneurysms admitted at the Kenyatta National Hospital, Nairobi, Kenya, from January 1998 to December 2007 were examined for presentation, diagnosis, risk/comorbid factors, site, age, and gender distribution. Data were analyzed using SPSS 13.0 and presented using tables. Results: Femoro-popliteal aneurysms constitute 33 out of 96 of peripheral cases (34.4%). The most common presentations were pulsatile mass (48.5%) and pain and swelling (33.3%). Pain alone and bleeding occurred in 9.1% each. Diagnosis was performed through Doppler ultrasound (45.5%), angiography (30.3%) and ultrasonography (24.3%). Aneurysms were associated with trauma (51.5%), atherosclerosis (21.2%), smoking (9.1%) and hypertension (6.1%). Site distribution was common femoral (33.3%), superficial femoral (36.4%) and popliteal (30.3%). Mean age was 46 years (range 13-79 years); with 20 (60.6%) of them occurring in individuals aged 50 years and younger. Male:female ratio was 15:1. Conclusion: In the present study, femoro-popliteal aneurysms constituted less than 40% of peripheral aneurysms, and superficial femoral artery was the most common site. They occurred predominantly in males aged 50 years and younger and were associated mainly with trauma and atherosclerosis. Prevalence, site and age distribution of these aneurysms in the Kenyan population differs from that described in studies of Caucasian populations.